Organic Liquid Fertilizer Coupled With Single Application of Chemical Fertilization Improves Growth, Biomass, and Yield Components of Cotton Under Mulch Drip Irrigation - Shi, Xiao-juan; Hao, Xian-zhe; Li, Nan-nan; Li, Jun-hong; Shi, Feng; Han, Huan-yong; Tian, Yu; Chen, Yun; Wang, Jun; Luo, Hong-hai (Frontiers in Plant Science, 2022)
Excessive fertilization, low nutrient utilization rate and continuous deterioration of cotton field environment have adversely affected the sustainable development of cotton in Xinjiang province of China. To overcome these issues, we hypothesized that an appropriate combination of liquid organic fertilizer and chemical fertilizer would effectively reduce chemical fertilizer input without sacrificing cotton quality and yield. Two-year field experiment explores the effects of three fertilization treatments on cotton growth, biomass accumulation and yield. The three fertilization treatments i.e., no application of fertilizer (CK), the single application of chemical fertilizer (CF), and the combined application of organic liquid fertilizer and chemical fertilizer (F0.6-F1.4) were set up in five ratios. Compared with CF treatment, the combined application of organic liquid fertilizer and chemical fertilizer treatments (F0.6-F1.2) speeded the growth period of cotton by 2-7 days with increased plant height, stem diameter, function leaf width, and more number of branches with a 9.7%-23.5% and 8.4%-28.5% higher total plant biomass and reproductive organs biomass, respectively. Compared with CF treatment, the rapid growth duration and maximum accumulation rate of reproductive organs were the highest in F0.8 treatment, with an average increase of 4.6 d and 20.3%; Increment in biomass accumulation contributed to an average increase of 21.8% and 18.9% in cotton boll number and yield under F0.8 treatment. Principal component analysis shows that the total biomass, reproductive organ biomass and total bolls per unit area were positively correlated with the yield, while stem diameter and vegetative organ biomass are negatively correlated with the yield. Conclusively, under film mulching drip irrigation, organic liquid fertilizer combined with CF reduced by 20% (F0.8 treatment, N, P2O5 and K2O were 182, 104 and 76 kg hm-2, respectively) can sustain the normal growth, promote reproductive organs biomass accumulation leading to efficient cotton production.